Effect of hydraulic retention time on the treatment of real cattle slaughterhouse wastewater and biogas production from HUASB reactor - Musa, Mohammed Ali; Idrus, Syazwani (MDPI, 2020)
Anaerobic digestion technology provides an alternative route for sustainable management of organic waste. In this study, the performance of the hybrid upflow anaerobic sludge blanket (HUASB) reactor consisting of synthetic grass media as attached growth surface was investigated for the treatment of cattle slaughterhouse wastewater under mesophilic (35 ± 1 °C) condition. After acclimatization with synthetic wastewater, the reactor was loaded up to OLR 10 g L−1d−1, corresponding to 20 g COD/L at a varying hydraulic retention time (HRT) of 24, 30, 36, 42, and 48 h. The system attained a maximum COD removal efficiency of 97% total suspended solids (TSS), volatile suspended solids (VSS), fats, oil, and grease (FOG), color removal, and turbidity were found as 97%, 284 mg/L, 79%, 78%, and 91% respectively. The biogas production after 48 h was found as 38 L/d, with about 85% methane and specific methane production of 0.24 LCH4/gCODadded. The ratio of alkalinity was 0.22, while ammonia nitrogen concentration reached a maximum of 839 mg/L at a steady state. Scanning electron microscopic (SEM) analysis revealed a predominance of Methanosarcina bacteria with the coccoidal shape at the end of the performance study. Therefore, the results of the experiment showed that increasing HRT significantly affects the performance of the system.